Biogenic Silica Extracted from Salacca Leaves Ash for The Adsorption of Salycilic Acid - Is Fatimah; Faiha Ulfiyani Zaenuri; Lolita Narulita Doewandono; Amri Yahya; Putwi Widya Citradewi; Suresh Sagadevan; Won-Chun Oh (Science and Technology Indonesia, 2021)
Extraction of biogenic silica from Salacca leaves ash and it’s utilization as adsorbent for salycilic acid has been successfully conducted. The caustic extraction by Refluxing the ash in NaOH followed by slow titration using acid produced the silica gel, and in order to evaluate the physicochemical character for adsorption purpose, the sintering of the dried gel was varied at 300, 400 and 500oC. Instrumental analysis of x-ray diffraction, scanning electron microscopy, gas sorption analysis, and Fourier transform infrared spectroscopy were employed. The kinetics of the salycilic acid adsorption was investigated in a batch adsorption system and the quantitative analysis was based on UV–Vis spectrometry. The results showed that the produced silica exhibited adsorption capability for salycilic acid in an aqueous solution. At varied sintering temperature, the highest adsorption capacity and affinity was achieved by temperature of 500oC, and the adsorption kinetics obeyed the Langmuir isotherm. The varied pH for adsorption suggested neutral pH is the most feasible compared to the acidic and basic conditions.